The Only Thing Constant is Change: Temporal Analyses of Racial/Ethnic Sentencing Disparities - Holmes, Bryan (American journal of criminal justice, 2023)
Over the last several decades, federal courts have devoted considerable effort towards improving fairness in sentencing. Despite these efforts, research has consistently shown that racial/ethnic minority defendants receive harsher sentences than similarly situated White defendants. While a large body of research has detected these racial/ethnic disparities, relatively few studies have examined how they have changed over time in light of the different legal, societal, and priority changes in federal criminal courts (and the United States more broadly). Using 22 years of federal sentencing data, the current study assesses trends in Black-White and Hispanic-White sentencing disparities (net of factors relevant to sentencing). Results suggest that trends in racial/ethnic sentencing disparities differ by the dependent variable examined. At incarceration, Black and Hispanic disadvantages have been largely time stable. However, racial/ethnic effects on sentence length have changed over time, diminishing in early years before re-aggravating in later years. Findings suggest that the movement towards racial/ethnic equity in sentencing has been slower than many might hope, with setbacks along the way. The re-emergence of racial/ethnic disadvantages indicates the need for a renewed focus towards reducing racial/ethnic disparities and creating greater egalitarianism in sentencing.